Ultrasensitive determination of microribonucleic acids in cancer cells with nanostructured-disposable electrodes using the viral protein p19 for recognition of ribonucleic acid/microribonucleic acid homoduplexes. (1st February 2018) - Zouari, M.; Campuzano, S.; Pingarrón, J.M.; Raouafi, N.
Abstract: This work describes the development of a simple and ultrasensitive electroanalytical methodology for the determination of microribonucleic acids (miRNAs) making use of nanostructured disposable electrodes. The strategy involves direct hybridization of the target miRNA (miRNA–21) with a specific thiolated RNA probe self-assembled together with mercaptohexanol (MCH) onto gold nanoparticles (AuNP)-modified screen-printed electrodes (SH-RNA/MCH-AuNP-SPCEs). In addition, the resulting RNA/miRNA homoduplexes are recognized with the viral protein p19 and labeled with a HRP-conjugated anti-Maltose Binding Protein (MBP) monoclonal antibody. Amperometric detection was carried out at −0.20 V ( vs . the Ag pseudoreference electrode) using the H2 O2 /hydroquinone (HQ) system. The prepared biosensors showed a linear dependence between the measured cathodic current and the concentration of the target miRNA over the 0.5–50 pmol L −1 range with a calculated detection limit (LOD) of 142 fmol L −1 without any target miRNA amplification. The assay lasted 60 min once the SH-RNA/MCH-AuNP-SPCEs were prepared. The SH-RNA/MCH-AuNP-SPCEs bioplatforms exhibit at least 2 months-storage stability and possess attractive practical advantages compared with other methods involving either p19 protein or amplification techniques. The usefulness of the method was demonstrated by determining the endogenous level of the target miRNA in total RNA (RNAt ) extracted from healthy and cancerous breast cells. Graphical abstract: Disposable biosensors for simple, rapid and sensitive determination of miRNAs in cancer cells based on their direct hybridization and efficient labeling of the RNA/miRNA homoduplexes formed with viral protein p19 and an HRP-labeled antibody at SH-RNA/MCH-AuNP-SPCEs.Image 1